Health Communication: Effects of Training Communicators in a Rural Area of Colombia - Vélez-Botero, Helena; Guerrero González, Abel; Bohórquez Buitrago, John (Revista Española de Comunicación en Salud, 2025)
Introduction: Developing competencies for mental health care communication in media is fundamental, and Protection Motivation Theory (PMT) provides a model to guide the design of communicative interventions. Objective: To evaluate the effectiveness of training to improve communicators competencies in designing effective strategies for mental health care in Colombian rural populations. Methodology: A convergent mixed methods study was conducted, integrating quantitative data (pre- and post-intervention questionnaires) and qualitative data (participant observation and follow-up focus group). Results: A statistically significant increase in the evaluated competencies was evidenced (from 4.6 to 7.5 points, p
Keywords: health communication; protection motivation theory; mental health